Development of Social Work Supervision in China: Mapping the Key Issues and Four Future Trajectories - Hou, Ming; Reevany Bustami, Mohammad (Asian Social Work Journal, 2025)
This study aims to review the problems and challenges faced in the development of social work supervision in Mainland China. A literature review was conducted following the PRISMA guidelines, utilizing four databases (PubMed, CNKI, SCOPUS, and WOS), and included 46 articles. Using thematic analysis, key themes were extracted from the research findings, focusing on the problems and challenges of an underdeveloped supervision system, role confusion, professional constraints, and cultural sensitivity in China's social work supervision system. This literature review emphasizes the necessity for the development of social work supervision in China, summarizes the problems and challenges faced, and proposes localized solutions. It also suggests future research directions for supervision in Mainland China.